Opening Speech – 29th Annual General Conference of LIBER - Mittler, Elmar (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
It is a great pleasure for me to welcome you all to the 29th Annual General Meeting of LIBER in the Royal Library of Copenhagen. As a group of about 160 delegates from Dublin and Lisbon to Moscow and Istanbul, from Bergen to Malta we represent Europe in its unity as well as in its diversity.